Allah is known through reason - Yahya, Harun, 1956-; Okur Production (Istanbul : Okur Production, 2000)
This film makes audience aware of His existence by think about the things around us. It also summons you to ponder over the universe and living beings and see how they have been created flawlessly. By showing a few of the countless signs of Allah in nature it will make you think about His power and knowledge over all things.
Keywords: Creation (Islam); God (Islam)